Early nursing assessment of overt shock in encephalitis: A case report - Nurul Anisa; Flaviliant Nurul; Asep Kartiwa; Ayu Prawesti Priambodo; Ristina Mirwanti (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Encephalitis can quickly progress to a life-threatening, multisystem seizure, accompanied by septic shock, disseminated intravascular coagulation (DIC), and severe respiratory failure. In such conditions, early detection by nurses is essential to recognize clinical deterioration and support timely intervention. Purpose: To analyze the contribution of early detection of nursing in recognizing overt shock in young adult patients with encephalitis who experience complications of septic shock and DIC. Method: The study used a descriptive case report design on a 22-year-old male patient who was treated in the emergency unit and intensive care unit of a tertiary referral hospital in March–April 2026. Data were obtained retrospectively from medical records, nursing records, laboratory results, radiological examinations, blood gas analysis, and therapy documentation. Results: Preliminary findings showed severe hemodynamic instability with blood pressure of 65/36 mmHg, pulse of 128 times/minute, respiratory rate of 29 times/minute, and lactate of 7.47 mmol/L. During treatment, progressive thrombocytopenia, coagulation disorders, decreased neurological status, and refractory hypoxemia were found. Mechanical ventilation and pronation position increased oxygen saturation from 84% to 98%, while lactate levels decreased to 2.26 mmol/L after intensive administration. Conclusion: Continuous nursing monitoring plays a role in accelerating resuscitation, vasopressor administration, ventilation support, and multidisciplinary coordination. Early detection of nursing plays an important role in recognizing overt shock, monitoring multisystem deterioration, and improving clinical stabilization and patient safety.